The Legality of Marriage According to Customary, Religion and State Laws: Impacts on Married Couples and Children in Manggarai - Yohanes S Lon (Jurnal Dinamika Hukum, 2019)
This study explores the complexity of marriage for people in Manggarai. Since they are citizens of the cultural community of Manggarai, Indonesian citizens, and members of a Catholic community, their marriage is required to follow the provisions of customary law, religious law, and state law. Using a library and ethnographic approaches, the study compares these laws on the legality of marriage and analyzes their differences and the impacts on the rights and obligations of married couples and children born to the couple. The study discovered that the differences in the provisions regarding the validity of a marriage between the three laws have provided space for the emergence of legal uncertainty and discriminatory treatment of customary marriages which are not legalized by religious law and state law as well as marriages that are divorced civilly but are still valid according to Catholic rules. Such a phenomenon is certainly a portrait of failure or incompetence in the attempt to unify marriage law in Indonesia through Law No. 1 of 1974 concerning Marriage. So it is urgent to have a more comprehensive new law that accommodates the wisdom of local customary law and provides protection for every citizen